“The Staff of Isaiah”: Catacomb Discourse in Arseny Tarkovsky’s Poetry - Medvedev, Aleksandr A. (Izvestiâ Uralʹskogo federalʹnogo universiteta. Seriâ 2, Gumanitarnye nauki, 2022)
This article analyses the work of A. Tarkovsky (1907–1989), for whom 1917 became a turning point which subsequently determined his “internal emigration”. The most important creative mission for Tarkovsky was the restoration of the interrupted cultural tradition of Russian modernism. As its representative, Akhmatova is a model of the creative and ethical behaviour of the artist for Tarkovsky. Tarkovsky’s poetry from the 1930s–1960s is considered from the point of view of the catacomb secret discourse (coding, subtext, background). Through images of the desert, sand, heat, and closed eyes, it expresses alienation from new culture and politics, a stoic opposition to oblivion, and desire to preserve cultural memory (Mandelstam, Tsvetaeva) that binds history into a single whole. In the situation of a cultural desert, such values as an individual’s dignity, Christian humility, and life are significant for Tarkovsky. In his model of the poet, Tarkovsky focuses on the biblical and early Christian tradition, in which the poet appears as a prophet, messiah, spiritual leader of the people (Isaiah, John the Baptist, Christ), emphasising not mystical or ritual but social ethics, characteristic of the Russian intelligentsia of the nineteenth century, with its moral uncompromisingness (“straight” ways). An important context for understanding Tarkovsky’s catacomb discourse and his image of the poet is the reflection on the people and the intelligentsia in L. Chukovskaya’s Notes on Anna Akhmatova (1938–1966). Polemising with the Narodism rejection of the intelligentsia in the Soviet period, Akhmatova and Chukovskaya express the key values of the Russian intelligentsia of the nineteenth and early twentieth centuries (personal dignity, freedom, ethical uncompromisingness, criticism of ethical relativism, truth and justice, prophetic ministry, sacrifice, and poverty). Tarkovsky’s poetic discourse and his image of a prophet poet also oppose Narodism simplification expressing the core values of the Russian intelligentsia and preserving the modernist complexity of poetics (openness and involvement in world culture, intertextuality, neomythologism, and associativity).